TUTURAN ILOKUSI JENIS EKSPRESIF DALAM NOVEL AYAHKU BUKAN PEMBOHONG KARYA TERE LIYE - Sari, Riski Monno; Ecca, Suleha; Saifullah; Hanafi, Muhammad (Universitas Muhammadiyah Surabaya, 2024)
Understanding expressive illocutionary speech increases the ability to feel and understand the feelings of others, helping to increase empathy and interpersonal support. Overall, a good understanding of expressive illocutionary speech is an important aspect in building effective communication skills and maintaining healthy social and emotional relationships. The importance of understanding expressive illocutionary speech lies in the ability to strengthen interpersonal relationships and prevent miscommunication. In this research, the researcher focuses on expressive illocutionary speech acts with the aim of: (1) Analyzing the function of expressive speech acts in the novel